Relative Contribution of Acetabular and Femoral Reconstruction to Prosthetic Joint Instability Risk after Primary Total Hip Arthroplasty - Ituarte, Felipe; Aggarwal, Ajay; Leary, Emily V.; Hansen, Benjamin J.; Keeney, James A. (The Journal of Hip Surgery, 2019)
Prosthetic joint instability is a challenging concern for a minority of total hip arthroplasty (THA) patients. Placement of the acetabular component within the traditional safe zone does not eliminate dislocation, and the relative contribution of femoral length and offset to instability risk has not been well defined. The authors compared 53 dislocated primary THAs treated against an age- and gender-matched cohort of 134 stable primary THAs. Anteroposterior and cross-table lateral radiographs were used to determine whether reconstructions met targets for acetabular inclination (30–50 degrees), acetabular anteversion (5–30 degrees), femoral length (0–9.9 mm) and femoral offset (0–9.9 mm). Statistical analysis was performed to assess univariate and multivariate relationships with an instability event; statistical significance was set using a two-sided p-value < 0.05. Forty-seven (88.7%) of the dislocating hips had nonoptimal acetabular or femoral reconstructions. While a similar proportion of patients in the study and control groups had acetabular reconstruction within the safe zone (51.5 vs. 47.2%, p = 0.63) patients with unstable hips were more likely to have acetabular component inclination outside of the target zone (30.2 vs. 7.5%, p < 0.01), acetabular anteversion < 15 degrees (30.2 vs. 3.7%, p < 0.0001), reduced femoral length (35.9 vs. 3.7%, p < 0.0001), and reduced femoral offset (41.5 vs. 7.46%, p < 0.0001). Stepwise multivariate logistic regression was performed and identified femoral head size less than 32 mm (OR 2.9, 95% CI 1.4–6.2) and higher inclination angle (OR 1.1, 95% CI 1.04–1.2) as significant independent risk factors for hip instability. The authors' study findings suggest that insufficient acetabular anteversion, femoral length, and femoral offset reconstruction contribute significantly to instability risk following THA. Using a larger femoral head is protective, but should be balanced against long-term volumetric wear risk.
Keywords: total hip arthroplasty; prosthetic joint instability; dislocation; component malposition; femoral length